THE EFFECT OF THE AMOUNT OF SODIUM METOXIDE CATALYST AND HEATING TIME ON THE QUALITY OF SHORTENING PRODUCTS IN THE INTERESTERIFICATION PROCESS - Syafrinal; Riani, Pevi; Putri, Melysa; Futeri, Renny; Armin, M. Ikhlas; Gusfiyesi; Susanti, Arisa (Universitas Veteran Bangun Nusantara, 2025)
Shortening is a solid plastic fat product that is widely used as a raw material in the production of food products such as biscuits, cakes, bread, and pastries. PT X produces shortening from the interesterification reaction of Refined, Bleached and Deodorized Palm Oil. (RBDPO). In the shortening production process using the interesterification method, it will be influenced by the amount of catalyst added and the heating time. The objective of this research is to analyze the effect of the amount of sodium methoxide catalyst and heating time on the interesterification process of RBDPO on the quality of shortening products. By considering the parameters of Solid Fat Content (SFC) and Slip Melting Point (SMP), an optimal method can be developed to improve the quality and stability of the shortening product. The variations of sodium methoxide catalyst used are concentrations of 0.050%; 0.100%; 0.125%; 0.25%; 0.375%; 0.500%, while the variations in heating time are 50 minutes, 40 minutes, and 30 minutes. The results of the research conducted show that the interesterification process of RBDPO into a shortening product with very good quality is achieved by using sodium methoxide catalyst with a concentration of 0.250% and a heating time of 40 minutes, in accordance with the standards set by PT X for Solid Fat Content (SFC) and Slip Melting Point. (SMP).